Impact of nanotechnology in cancer: emphasis on nanochemoprevention - Siddiqui IA (Dove Medical Press, 2012)
Imtiaz A Siddiqui, Vaqar M Adhami, Jean Christopher Chamcheu, Hasan MukhtarDepartment of Dermatology, University of Wisconsin, Madison, WI, USAAbstract: Since its advent in the field of cancer, nanotechnology has provided researchers with expertise to explore new avenues for diagnosis, prevention, and treatment of the disease. Utilization of nanotechnology has enabled the development of devices in nanometer (nm) sizes which could be designed to encapsulate useful agents that have shown excellent results but otherwise are generally toxic due to the doses intended for extended use. In addition, examples are also available where these devices are easily conjugated with several purposeful moieties for better localization and targeted delivery. We introduced a novel concept in which nanotechnology was utilized for enhancing the outcome of chemoprevention. This idea, which we termed as "nanochemoprevention," was subsequently exploited by several laboratories worldwide and has now become an advancing field in chemoprevention research. This review examines some of the up and coming applications of nanotechnology for cancer detection, imaging, treatment, and prevention. Further, we detail the current and future utilization of nanochemoprevention for prevention and treatment of cancer.Keywords: nanochemoprevention, cancer, nanotechnology